Integrating Essential Practical Sessions into the Generic Elective Course in Physical Education Curriculum: A Case Study - P, Kumar; Ahlawat, Ravinder Pal; Bhukar, Jaiprakash; Kumar, Parveen; Dhull, Sandeep; Singh, Gajender; L, Ajithkumar; P, Kasthuri Thilagam (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
Physical education courses, traditionally a blend of theory and practice for their own department students, are often delivered as purely theoretical classes for students from non-physical education disciplines enrolled in Generic Elective Courses (GEC). This approach can lead to disengagement and boredom, as students are already exposed to multiple theoretical classes throughout the day. To address this issue, the Department of Physical Education at the Central University of Haryana revised its GEC curriculum to include practical sessions alongside theoretical content. This study explores the impact of this curriculum revision on student engagement and physical fitness. Feedback from 200 postgraduate students, aged 20-25, indicated a strong preference for incorporating practical sessions into the curriculum, with 98% of respondents favoring this change. The revised curriculum allocated two hours per week for physical activities, aimed at enhancing student engagement and promoting the importance of physical fitness. The effectiveness of the new curriculum was assessed through a one-minute push-up test, measuring upper body strength at the beginning and end of the semester. Initial results showed that 50% of the students struggled to complete the test. However, by the end of the semester, 96% of students successfully completed the one-minute push-up test, indicating significant improvement in physical fitness. The study concludes that integrating practical sessions into GEC physical education courses not only improves student engagement but also enhances physical fitness. It highlights the need for a balanced approach, combining theory with hands-on activities, to foster holistic development. The findings suggest that other departments offering practical-oriented courses could benefit from incorporating similar practical components into their curricula.